American Indian Stereotypes in the World of Children: A Reader and Bibliography - Hirschfelder, Arlene; Molin, Paulette F.; Wakim, Yvonne; Dorris, Michael A. (Rowman & Littlefield Publishers, 1999)
The world of contemporary American infants and young children is saturated with inappropriate images of American Indians. American Indian Stereotypes in the World of Children reveals and discusses these images and cultural stereotypes through writings like Kathy Kerner's previously unpublished essay on Thanksgiving and an essay by Dr. Cornell Pewewardy on Disney's Pocahontas film. This edition incorporates new writings and recent developments, such as a chronology documenting changes associated with the mascot issue, along with information on state legislation. Other new material incorporates powerful commentary by Native American veterans, who speak to the issue of stereotyping against their people in the military. Also includes a new expanded annotated bibliography.